Role Emotion Intelligence Towards Work-Life Balance with Support Family as Mediator Variables - Sembiring, Ardha Aulia Rovica Br; Hardjo, Suryani; Lubis, Rahmi (Kuras Institute, 2024)
The purpose of this study was to analyze the role of emotional intelligence on work-life balance with family support as a mediator variable in pamong praja police unit employees in North Sumatra. This research uses a quantitative approach based on the ideology of positivism, with a population of 836 employees and a sample of 223 employees of the Pamong Praja police unit who work in the Public Order and Community Peace Division in Medan City and in Binjai City, using purposive sampling techniques, data collection using SEM-PLS research tools to test the hypotheses that have been prepared and the study employs three scales instrument: Work-Life Balance rooted in Fisher, Smith, and Burger's dimensions. Emotional Intelligence utilizing Goleman's model. Family Support is refined from Sarafino and Smith's framework, emphasizing emotional, instrumental, informational, and mentoring support dimensions. Based on the results of the study, it is obtained that there is an influence of emotional intelligence on family support, there is an influence of family support on work-life balance, there is an influence of emotional intelligence on work-life balance, family support significantly mediates the relationship between emotional intelligence and work-life balance. It is hoped that institutions will continue to improve policies to pay attention to the welfare of their employees, such as attention to working hours, changing work assignments, rewarding achievements, and health services. Insurance and appropriate salary increases. The findings in this study can provide new nuances for science, especially psychology.